Radiographic evidence to help predict the mechanism of injury of pediatric spiral fractures in nonaccidental injury. - O'Connor-Read, L; Teh, J; Willett, K (2007)
BACKGROUND: Spiral fractures are one of the most common fractures seen in nonaccidental injury. With radiographic evidence for the mechanism of injury, the physician is more capable of identifying any inconsistencies in the history. OBJECTIVES: To detail and differentiate the fracture patterns created by rotation forces in different directions. To determine the reliability of that recognition method applied to standard radiographs. METHODS: Twenty rabbit femurs were fractured using a torque transducer and imaged using standard anterior-posterior and lateral radiographs. The ability of pediatric, orthopaedic, emergency department, and radiology doctors to correctly predict the mechanism of force required to produce the fracture was assessed before and after being given the findings of this study. RESULTS: The radiographic propagation of the spiral fractures was consistent and followed 6 simple principles. There was a statistically significant difference in the numbers of correctly diagnosed radiographs by these doctors before and after the explanation of our findings (chi2 = 14.06; df = 1; P = 0.002). CONCLUSIONS: The direction of the torsional force producing spiral fractures can be determined from characteristic features on routine anterior-posterior and lateral radiographs. Determining the direction of the torsional force on radiographs does not always seem to be intuitive. These derived 6 principles will be a useful aid to physicians who manage pediatric spiral fractures where nonaccidental injury is being considered.